PENJUALAN OBYEK HAK TANGGUNGAN DIBAWAH TANGAN UNTUK PENYELESAIAN KREDIT MACET DI BANK (Lex Journal: Kajian Hukum & Keadilan, 2018)
Giving credit is not always smooth. There is often a risk of blocking in the credit repayment. The granting of credit must be accompanied by the granting of collateral by the debtor, the credit becomes stalled then the Bank must immediately seek efforts to be able to save the credit.               Based on explanation above, the reseach problem is : How to selling the Object  of  mortage under hand to solve bad credit in bank ?. The research method implied  is  normative.  The  problem  approach is done by statute, philosophy and conceptual approach.               The Bank chooses a settlement through a sales mechanism under-handedly, compared to the auction process. This is done since selling mortage under the hands is more practical than through the auction process. Selling mortage object under-handedly provides benefits for both creditors and debtors. The advantages obtained are as follows:1. Creditora. Shorter time;b. The cost is cheaper;c. It maintains good relationship with the debtor or other related parties.2. Debtorsa. Selling price is highb. getting the rest of the moneyKeywords :Sale under the hands, the object of mortgage, bad credit.